Розробка сайту підбору та обговоренняонлайн серіалів - Сазонов, В. О. (ХНУРЕ, 2024)
This report relates to the development of information system components for the creation of an online series platform. The project is a website where users can review various TV series. Among the categories available are genres such as drama, comedy, science fiction, and more. Users are able to find specific shows, rate them, and share comments. The aim of the project is to provide the audience with a convenient platform to watch online TV series, share comments and find the best new releases in the world of online content.
Keywords: підбір серіалів; обговорення серіалів; онлайн платформа; рекомендації серіалів; веб-дизайн серіалів